COMBINATION OF N-BUTANOL GOTU KOLA EXTRACT, N-BUTANOL LERAK EXTRACT, AND NEEM SEED OIL IN A NANOSTRUCTURED LIPID CARRIER HERBAL ANTIMICROBIAL SPERMICIDE - Sukarjati; Wisnu Kusuma, Pungky Slamet; Rahayu, Asti Rahayu (jfpublisher, 2023)
Introduction. The spermicidal effect of the nonoxynol-9 compound paralyzes sperm by rupturing the cell membrane. Nonoxynol-9 compounds, however, can irritate and itch the vagina. Using a Nanostructured Lipid Carrier (NLC) delivery system, alternative herbal spermicides were created in this research using gotu kola, lerak, and neem. To optimize and formulate of NLC formulation herbal spermicides made from a combination of lipids on Glyceryl Monostearate (GMS) and liquid lipids of olive oil using a response surface full factorial design model (22), and analyzing particle size tests, spreadability tests, pH, viscosity, and potential zeta tests. Method. A full factorial design model (22) was employed in this research to optimize and formulate NLC herbal spermicides using a combination of lipids in Glyceryl Monostearate (GMS) and liquid lipid olive oil. Results and Analysis. NLC herbal spermicide particle sizes range from 103.8 ± 0.3 to 178.0 ± 1.2 nm. The spreading power of NLC Herbal Spermicide ranges from 5.8 ± 0.05 to 6.3 ± 0.05 cm. The Zeta Potential of NLC Herbal Spermicide has a range of -17.0 ± 0.8 to -24.8 ± 3.3 mV. Resulting pH range is 5.7 ± 0.2 to 6.5 ± 0.1, resulting viscosity is 564 ± 0.3 to 661 ± 0.5 cps. Discussion. The equation model for the power distribution response has a p-value smaller than 0.05 which means it is significant so that the equation model can be used to predict the power response. Different things occur in the zeta potential response and spreadability which have a p-value greater than 0.05, so it can be concluded that the ratio of solid lipids and liquid lipids has no effect on the particle size and zeta potential parameters.